Effect of fetoscopic laser surgery on the placental characteristics and birth-weight discordance of twins with twin-to-twin transfusion syndrome - Wang, Xueju; Li, Luyao; Yuan, Pengbo; Zhao, Yangyu; Wei, Yuan (Frontiers in Medicine, 2022)
Objective This study explored the effect of fetoscopic laser surgery on the placental structure and birth-weight discordance of TTTS. Methods A retrospective cohort study was conducted in TTTS patients who were admitted to the Peking University Third Hospital between April 2014 and April 2020. The patients were divided into two groups: laser group and control group. Placentas with twin survival were injected, and pregnancy outcomes and placental characteristics of the two groups were compared. The correlation between the birth-weight discordance and placental characteristics in each group was analyzed. Results: The gestational age at first diagnosis in the laser group was significantly smaller than that in the control group (21.6 ±2.8 weeks vs. 27.7 ±3.0 weeks, p < 0.001). The proportion of patients with TTTS stage-I in the laser group was significantly lower than the control group (9.4% vs. 64.0%, p < 0.001). The gestational age at delivery in the laser group was significantly larger than that in the control group (33.6 ±2.1 weeks vs. 31.4 ±2.5 weeks, p = 0.001). In the laser group, the birth-weight discordance ratio was positively correlated with the placental territory discordance ratio (Spearman coefficient = 0.556; p = 0.001). Conclusions The birth-weight discordance is positively correlated with placental territory discordance in TTTS patients after FLS.